The equation of the perpendicular has slope 1/3 so the equation of the perpendicular is:

y-2=(x+6)/3 that is y=x/3+4. This meets y=-3x+4 when -3x+4=x/3+4, i.e., x=0 and y=4.

So now we work out the distance between (0,4) and (-6,2): √6²+2²=√40=6.325 approx.

- All categories
- Pre-Algebra Answers 12,330
- Algebra 1 Answers 25,321
- Algebra 2 Answers 10,467
- Geometry Answers 5,194
- Trigonometry Answers 2,642
- Calculus Answers 6,033
- Statistics Answers 3,029
- Word Problem Answers 10,149
- Other Math Topics 6,687

81,852 questions

86,192 answers

2,224 comments

69,804 users